Transformasi Sistem Ekonomi Syariah dalam Penyediaan Rumah Tapak Bagi Masyarakat Berpenghasilan Rendah Studi Pada PT. Herijaya Asri Sentosa di Kabupaten Sambas - Teguh Hendi Nugroho; Tehedi; Neli (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2024)
This study is based on the phenomenon that sharia property has emerged as an option for the community, especially for those who want to buy a house or just invest, making the community, especially Muslims, feel much more comfortable because they can avoid usury which is prohibited in Islam. The focus of this study is: 1) What is the Form of Sharia Economic Transformation in the provision of Landed Houses for MBR at PT. Herijaya Asri Sentosa? 2) How is the Review of Sharia Economics on the Transformation of Sharia Economics in the provision of Landed Houses to Low-Income Communities at PT. Herijaya Asri Sentosa? This study uses a qualitative approach and a case study research type. Data collection techniques through interviews, observation and documentation. Data analysis uses an interactive analysis model that includes data reduction, data display, and verification/drawing conclusions. The results of the study show the following: 1) The Form of Sharia Economic Transformation in the provision of Landed Houses for MBR at PT. Herijaya Asri Sentosa is to have a murabahah/sale and purchase agreement. Where, the owner of PT. Herijaya Asri Sentosa sells finished housing units through Conventional Banks/BNI Bank. Then, PT. Herijaya Asri Sentosa applies a sharia system to its consumers by not applying usury, tadlis and gharar in its sales process. The process of buying and selling houses based on sharia principles uses a sale and purchase agreement agreed upon between the owner and the buyer. 2) Review of Sharia Economics on Sharia Economic Transformation in the provision of Landed Housing to low-income communities at PT. Herijaya Asri Sentosa is in accordance with sharia economics. Where in this case, there are no elements of usury, tadlis, and no elements of gharar in the transaction process or its implementation. There is no interest or fine given to consumers, only a take over system if the consumer is unable to pay for more than 3 times due. This is because interest and fines are not in accordance with applicable Islamic law.